2010
DOI: 10.1007/s00213-010-1876-x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose effects on long-term memory performance: duration and domain specificity

Abstract: Improved implicit memory performance following glucose administration has not been reported before. Furthermore, the current data tentatively suggest that level of processing may determine the required glucose dosage to demonstrate memory improvement and that higher dosages may be able to exert effects on memory pertaining to both hippocampal and non-hippocampal brain regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…These effects have been demonstrated repeatedly previously in relation to dieting and fasting (Benton & Parker, 1998;Green, et al, 1997;Green & Rogers, 1995;Hagan, et al, 2000;Keys, et al, 1950;Laessle, et al, 1996;McFarlane, et al, 1999;Sunram-Lea, et al, 2010), and are demonstrated here after just one and two days of fasting.…”
Section: Discussionsupporting
confidence: 85%
“…These effects have been demonstrated repeatedly previously in relation to dieting and fasting (Benton & Parker, 1998;Green, et al, 1997;Green & Rogers, 1995;Hagan, et al, 2000;Keys, et al, 1950;Laessle, et al, 1996;McFarlane, et al, 1999;Sunram-Lea, et al, 2010), and are demonstrated here after just one and two days of fasting.…”
Section: Discussionsupporting
confidence: 85%
“…Based on the findings of Parent et al (2011), that glucose was capable of increasing neural activity across a network of brain regions, it is possible that in the current study, glucose administration also influenced brain regions outside the hippocampus. Evidence that glucose can improve cognitive functions, including tracking and implicit memory, which do not depend on the hippocampus (Owen et al, 2010;Riby et al, 2008;Scholey et al, 2001Scholey et al, , 2006Scholey et al, , 2009, indicates It is likely that glucose is capable of influencing cognitive processes mediated by neural regions outside the hippocampus.…”
Section: Discussionmentioning
confidence: 98%
“…Observations of glucose improvements to declarative LTM have led to the suggestion that there is a preferential effect of glucose administration on processes related the conscious, recollective fraction of memory (Riby, 2004). In support of this premise, glucose ingestion has been demonstrated to improve performance on explicit word recall tasks (Foster et al, 1998;Manning et al, 1997), although other studies have revealed benefits to measures of implicit memory (Angelie et al, 2001;Owen et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…Immediately after drink consumption, the mood scale was administered again. Analogous to the procedure of previous studies (e.g., Foster et al 1998;Owen et al 2010;Sünram-Lea et al 2010, 2002a, the first cognitive test was carried out 20 min after drink consumption (in order to ensure successful transfer of glucose to brain). Blood glucose measurements were taken at baseline and approximately 15, 35, and 48 min after drink administration.…”
Section: Methodsmentioning
confidence: 99%